DEVELOPMENT AND VALIDATION OF NEW SPECTROPHOTOMETRIC METHODS FOR ESTIMATION OF ANTIPSYCHOTIC DRUG ASENAPINE MALEATE IN PURE AND DOSAGE FORMS - EL-SHEIKH, RAGAA; ELLATEIF, AHLAM E. ABD; AKMAL, ESRAA; GOUDA, AYMAN A. (International Journal of Applied Pharmaceutics, 2020)
Objective: Three sensitive, simple, precise, reproducible, and validated spectrophotometric methods have been developed for the determination of anti-psychotic drug (asenapine maleate) in pure and pharmaceutical dosage forms. Methods: The methods are based on the formation of yellow-colored ion-pair complex between asenapine maleate and three acid dyes, namely, bromocresol purple (BCP), bromophenol blue (BPB) and bromothymol blue (BTB) with absorption maxima at 410, 414 and 416 nm, respectively. Several parameters such as pH, buffer type and volume, reagent volume, the sequence of addition and effect of extracting solvent were optimized. Results: Under the optimum experimental conditions, beer’s law is obeyed over the concentration ranges of 1.0–20, 1.0–14, and 1.0-16 μg/ml for BCP, BPB and BTB, respectively, with good correlation coefficients (0.9994-0.9998). The apparent molar absorptivity and Sandell’s sensitivity values are reported for all methods. The limit of detection (LOD) and the limit of quantification (LOQ) values are found to be 0.27, 0.30, and 0.25 μg/ml and 0.90, 1.0, and 0.83 μg/ml for BCP, BPB and BTB, respectively. The stoichiometric ratio of the formed ion-pair complexes was found to be 1:1 (drug: reagent) for all methods, as deduced by Job's method of continuous variation. Conclusion: The proposed methods were successfully applied for the determination of asenapine maleate in pharmaceutical formulations with good accuracy and precision. Statistical comparison of the results was performed using Student's t-test and variance ratio F-test at the 95% confidence level and there was no significant difference between the reported and proposed methods regarding accuracy and precision. Further, the validity of the proposed methods was confirmed by recovery studies via standard addition technique in accordance with ICH guidelines.